Krinagoras and Imperial Glory: An Interplay Between Irony, Mockery, and Flattery - Mitropoulos, Giorgos (Pnyx: Journal of Classical Studies, 2023)
This paper examines two epigrams of the Mytilenean poet Krinagoras (AP 9.562 and 9.224), traditionally interpreted as court flattery examples. Krinagoras was a poet close to the Augustan court, and many of his epigrams praised members of the imperial house. However, a closer examination of these epigrams reveals a discreet dose of irony towards the glory of Augustus, a seemingly strange choice on the part of a court poet of the Augustan circle. It seems that Krinagoras, who travelled from his native island Mytilene to the westernmost part of the Roman Empire in Tarragona as a member of the embassy to meet Augustus, used irony as a stylistic instrument to insinuate his discontent for the hardships he had suffered. The paper contributes to a growing literature that examines the ways literary works functioned as instruments of flattering the ruler but also concealed resentment or mockery, even against the Roman emperor. Krinagoras’ irony is merely one instance among many where subtle mockery and satire of the imperial family were exercised in the early Augustan period.